Process Quality Control of Eyeglass Lens Production to Reduce Particle Using Six Sigma and DMAIC - Wanto, Indra; Marlapa, Eri (ARE Publisher, 2025)
Objectives: The aim of this research is to examine and maintaining the high product quality while optimizing resource efficiency is a critical challenge in today’s competitive global market. PT XYZ, a leading ophthalmic lens manufacturer, struggles with particle defects, particularly in the UV coating process, which contributes to 80% of total production defects. Methodology: To address this issue, the study applies the Six Sigma methodology using the DMAIC framework to identify root causes, reduce defects, and improve production efficiency. This research adopts a quantitative approach with comparative and descriptive methods. Data collection methods include direct observation, focus group discussions, interviews, and historical data analysis. Findings: The initial analysis identified several defect sources, including environmental factors, improper process handling, and machine performance issues. Improvement actions, such as installing an antistatic blower and optimizing pre-cleaning processes, successfully reduced the defect rate from 12% to 4.7%. The Defects Per Million Opportunities (DPMO) dropped from 112,801 to 46,782, while the Sigma level improved from 2.71 to 3.18. Conclusion: This study conclude that implementing Six Sigma and DMAIC methodologies effectively enhances quality control in ophthalmic lens manufacturing. These improvements strengthen PT XYZ’s long-term competitiveness while supporting sustainable manufacturing practices aligned with SDG 9 (Industry, Innovation, and Infrastructure) and SDG 12 (Responsible Consumption and Production).